2022
DOI: 10.1093/ckj/sfac248
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil-to-lymphocyte and platelet-to-lymphocyte ratios: associations with mortality in a haemodialysis cohort

Abstract: Background Lymphocyte ratios reflect inflammation and have been associated with adverse outcomes in a range of diseases. We sought to determine any association between neutrophil-to-lymphocyte ratio (NLR) and platelet-to-lymphocyte ratio (PLR) and mortality in a haemodialysis cohort, including a COVID-19 infection subpopulation. Methods A retrospective analysis was performed of adults commencing hospital haemodialysis in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 37 publications
1
8
0
3
Order By: Relevance
“…Numerous studies have shown that the NLR is a convenient and cost-effective marker of inflammation 28 and an indicator of sarcopenia risk 15 . Previous research has evaluated the correlation between NLR and the risk of sarcopenia in different populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have shown that the NLR is a convenient and cost-effective marker of inflammation 28 and an indicator of sarcopenia risk 15 . Previous research has evaluated the correlation between NLR and the risk of sarcopenia in different populations.…”
Section: Discussionmentioning
confidence: 99%
“…These inflammatory cytokines inhibit protein synthesis, reduce muscle anabolism and damage energy homeostasis, leading to muscle atrophy and malfunction 11 . The neutrophil-to-lymphocyte ratio (NLR), which is derived from absolute neutrophil and lymphocyte counts, is a convenient and cost-effective measure of systemic inflammation 14 , 15 . A previous study indicated that NLR could offer valuable insights into inflammation among CKD patients, including those undergoing hemodialysis 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Further examples include platelet–lymphocyte ratio (PLR), monocyte–lymphocyte ratio and eosinophil–lymphocyte ratio, all of which have been tested for prognosticating COVID‐19 patients with varying degrees of success [99]. Recently, both NLR and PLR have shown prognostic value in COVID‐19 patients at haemodialysis initiation [104].…”
Section: Blood Testsmentioning
confidence: 99%
“…Similar findings have been observed in individuals with chronic kidney disease who contracted COVID-19[ 39 ]. A statistically significant increase in mortality was observed in patients undergoing HD with COVID-19 when NLR thresholds were set at ≥3.0 and ≥3.5[ 40 ]. Therefore, patients undergoing HD who contract COVID-19 require additional care because of their increased risk of death.…”
Section: Nlr and Hdmentioning
confidence: 99%